Análisis del funcionamiento de los motores de la piladora Ledesma Ramírez LANDRAM S.A. - Contreras Foyain, Juan Ernesto (2021)
The present case study was carried out in the Ledesma Ramírez LADRAN SA pile mill, which focused on the analysis of each of the machinery such as the 1.5 hp elevator motor, the stationary motor, and the 10 hp motor for peeling. of rice, the 15 hp motor that handles the chaff, 1.5 rice classifier motor among others. Which for the present study the field methodology was used, as well as the techniques of instruments such as the survey and the interview, this information was compiled with the help of all the employees who work within the organization. When carrying out the analysis of the motors in the respective organization, it was found that there are many anomalies such as voltage drop problems, cables not in accordance with the different electric motors, widely used bands, problems in bars and rotor sealing rings, there is no maintenance plan for the motors as well as the imbalance in the magnetic field. That is why it is very necessary for the authorities to be able to know the preventive protections that help to promote quality engines and can deliver better productivity during the work process.